The interactions of ‘Mandarin as a second language’ teachers in Content and Language Integrated Learning classrooms - Zhang, Teng (Curtin University, 2020)
The goal of this research was to investigate the process of Child Second Language Acquisition in Mandarin as a Second Language classrooms by employing a Content and Language Integrated Learning approach in Australia. Teachers’ interactions and students’ responses to these interactions during the class were examined. The findings show that teachers’ interactions facilitate Second Language Acquisition by using various strategies, meanwhile, the students’ responses display various patterns to support their second language learning.